2018
DOI: 10.1186/s12871-018-0497-5
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency power of heart rate variability can predict the outcome of thoracic surgical patients with acute respiratory distress syndrome on admission to the intensive care unit: a prospective, single-centric, case-controlled study

Abstract: BackgroundThe morbidity and mortality of acute respiratory distress syndrome (ARDS) remains high, and the strategic focus of ARDS research has shifted toward identifying patients at high risk of mortality early in the course of illness. This study intended to identify the heart rate variability (HRV) measure that can predict the outcome of patients with ARDS on admission to the surgical intensive care unit (SICU).MethodsPatients who had lung or esophageal cancer surgery were included either in the ARDS group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 44 publications
(42 reference statements)
1
20
0
Order By: Relevance
“…Also, Huang CT et al [14] concluded that spectral analysis of HRV in 101 patients admitted to the intensive care unit undergoing mechanical ventilation could predict the success or failure of removal of said support and that patients extubated with a lower HRV and a lower TP had a higher risk of reintubation after 72 hours. Chen IC et al [15] demonstrated, as in our study, that lower energy (total power) and higher vagal tone (HF) were independent predictors of mortality in patients with adult respiratory distress syndrome (ARDS).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Also, Huang CT et al [14] concluded that spectral analysis of HRV in 101 patients admitted to the intensive care unit undergoing mechanical ventilation could predict the success or failure of removal of said support and that patients extubated with a lower HRV and a lower TP had a higher risk of reintubation after 72 hours. Chen IC et al [15] demonstrated, as in our study, that lower energy (total power) and higher vagal tone (HF) were independent predictors of mortality in patients with adult respiratory distress syndrome (ARDS).…”
Section: Discussionsupporting
confidence: 76%
“…They also show that, in particular, low autonomic activity with depletion of the sympathetic component (LF) and proportionally greater parasympathetic tone (HF) can predict the risk of developing respiratory distress (ARDS) in patients on mechanical ventilation, the success or failure of removal of this support, and mortality in these patients [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…However, only three variables can be included in the multivariable analysis based on the rule of 10 events per variable (EPV-10), as in our previous study. 11 The candidate of mechanical ventilation measurements, included in the multivariable analysis, were the significant variables in the univariate analysis of differences between the two groups. Since these mechanical ventilation measurements were highly correlated with one another, principal component analysis (PCA) was performed to reduce the correlated variables to a small set of variables.…”
Section: Discussionmentioning
confidence: 99%
“…The reason have been presented in our previous article. 11 In order to resolve this issue, the PCA selection method, EPV-10 principle and Firth logistic regression of penalty likelihood approach were chosen in our investigation so that our findings could be substantiated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation